Innovation platforms for improved livelihoods and rainwater management in Ethiopia - International Livestock Research Institute; International Water Management Institute (International Livestock Research Institute, 2014)
This digital story was produced to communicate work done by the Nile Basin Development Challenge (NBDC), specifically activities undertaken by the team working on 'Technologies, Institutions and Policies'. The NBDC aimed to improve the livelihoods of farmers in the Ethiopian highlands through land and water management and was funded by the Challenge Program for Water and Food. For more information see: http://nilebdc.org